Honduras: The impact of COVID-19 and other shocks, and policy implications: Final report - Díaz-Bonilla, Eugenio; Flores, Luis; Piñeiro, Valeria; Centurión, Miriam (International Food Policy Research Institute, 2022)
Two previous reports (Díaz Bonilla, Laborde and Piñeiro, 2021, and Diaz-Bonilla, Flores, Paz, Piñeiro, and Zandstra, 2021) covered the evolution and impacts of the pandemic on food systems in Honduras until the time of their writings (which together cover from the start of the pandemic in early 2020 until October 2021). This third report concludes the assessment of the impact of the COVID-19 pandemic on food systems in Honduras, recapitulating the previous ones and updating the analysis until the end of May 2022. This country and its food systems, however, have been also affected by other events since the pandemic started in early 2020, such as the tropical storms Eta and Iota in November 2020. Subsequently, in 2021 the strong world economic rebound due to expansionary fiscal and monetary policies in the USA and other countries, generated strains on value chains, leading to increases in transportation costs and the prices of food, energy and fertilizers. In the case of agricultural products, those increases were compounded by adverse climate events in some important producing areas, particularly in South America. Finally, the Russian-Ukraine Conflict (RUC) on February 24, 2022, has added further pressures on prices of energy, fertilizers, and some food products (such as wheat and vegetable oils). Therefore, the specific impact of the pandemic on food systems in Honduras has been interacting with the other developments mentioned. From the point of view of policymakers, they need to respond to the overall impact of the conditions affecting the population, whatever the converging main causes may be. Therefore, this final report, while emphasizing those aspects linked to the pandemic will also discuss the overall conditions in Honduras, affected by those many factors. This report is structured as follows. First, it summarizes the main policy responses, costs, and financing related to the COVID-19 shock. Second, it brings up to date the evolution of the pandemic, using different indicators. Third, it updates the evolution of key economic and nutritional variables. Fourth, there is a brief discussion of the implications of RUC for food systems. Fifth, the report continues with a more specific analysis of the evolution of some food value chains that are central to food consumption in Honduras. The next section discusses policy considerations for health, poverty and nutrition, and food value chains, in light of the updated analysis. A final section concludes.